Rancang Bangun Sistem "Final Year Project" Sistem Manajemen Tugas Akhir Berbasis Wordpress - Naufal Bayuaji Pawenang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Victoria University Lecturers have problem regarding overseeing their students' final year project progress. Because of their tight schedule, lecturers tend to have some difficulties to monitor and review students' progress work. Students are also being bothered by the difficulties to dividing their final project tasks, which is being done in a team. Also, students need some kind of means to collect their progress work to be reviewed by the lecturers. After conducting interviews, the author suggesting a prototype for a final project management system. The â€œFinal Year Projectâ€ management system are designed to tackle those conditions. Some features in the management system are Attendance Record to record student attendance. Task management to help students allocating their tasks and Create New Project to help lecturers create their students' worksheet and allocating them. â€œFinal Year Projectâ€ system are built using Content Management Service (CMS) Platform WordPress. To test the system, the author using both white box testing and black box testing. Although the system works as intended, there is a room for improvement as reducing the dependency of using plugins because they tend to increase Coupling level and make it harder to documenting the system.